Angularly Resolved Deep Brain Fluorescence Imaging Using a Single Optical Fiber - Israel J. De La Rosa; Mehdi Azimipour; Patrick K. Cullen; Fred J. Helmstetter; Ramin Pashaie (International Journal of Optics)
In this article, we report the development of a minimally invasive fiber optic based fluorescence probe which can reach deep brain objects and measure the intensity and spatial distribution of fluorescence signals in the tissue. In this design, the brain is scanned by a single penetrating side-firing optical fiber which delivers excitation light pulses to the tissue at different depths and orientations and simultaneously collects samples of fluorescence emission signals. Signal-to-noise ratio of the measurements is improved by adapting the pulse compression technique and the theory of optimal filters. Effects of each design parameter on the overall performance of the scanner, including the spatial resolution and speed of scanning, are analyzed and experimentally measured. In vivo experiments show that the new device, despite the simplicity of the design, provides valuable information particularly useful in optogenetic stimulation experiments where the exact position of the fiber tip and the radiation orientation can change the outcome of a test.